Formation of Moderate Character in Pesantren - M. Soni Amrullah; Ahmad Wahyudi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Education is an effort made by an educator to his students so that students get optimal development. Educating children properly and optimally is the duty and responsibility of parents and educators at the same time. Pesantren is a sub-culture is faced with the demand to develop noble life values not only for Islamic religious affairs. Furthermore, the role taken is not only an effort to instill science to the students but also the cultivation of moderate character values and noble morals. This article with a theoretical approach seeks to analyze the efforts that have been made by pesantren so far in instilling moderate character values in their students as a methodological offer to instill moderate character values in a wider and more diverse scope. This research is library research. In this study, the author used text sources both primary and secondary related to Pesantren in an effort to instill moderate character education for students and analyze and examine important factors that can be used as a spur in instilling the value of religious moderation. The results obtained in the study are that there are four important factors in an effort to instill a moderate attitude in religion. First, the Sufistic paradigm that pesantren have, Second, the ethics and culture developed by pesantren, Third, curricular activities in the form of a moderate-minded yellow book study, Fourth, the vital role of kyai in pesantren can be a catalyst for the cultivation of moderate values